The Protection to Victims of Violence Based on Gender as a Fulfillment of the Constitutional Rights in the Perspective of Human Rights in Boyolali’s District, Indonesia - Yudhanti, Ristina; Arifin, Saru; Rismadini, Fauziah (JILS (Journal of Indonesian Legal Studies), 2017)
Cases of Gender-based violence increase from year to year and this raises concerns. The phenomenon that puts Boyolali as the district with the highest number of gender-based violence to former residency Surakarta need for follow up. This study aims to get information form of protection and the efforts that have been undertaken by the government of Boyolali District to meet the Constitutional Rights for victims of gender-based violence in Boyolali; Fulfillment of Constitutional Rights for victims of violence against women by the government of Boyolali Regency, among others; Complaint service spread in 19 districts in Boyolali District. Social Rehabilitation Services are given by officers and social rehabilitation. Spiritual guidance services provided by Spiritual guidance counselors are trained for women andChild victims of violence in the integrated service unit. Law enforcement from the level of investigation to court decisions on cases of violence against women and children has been carried out according to the procedure. Legal aid service to women and children of victims of violence. Repatriation of women and children Victims of violence. According to standard that has been set in SPM by 75%. Social re-integration services for women and child victims of violence, according to standards set out in the SPM at 100%